2006
DOI: 10.1080/02713680600681236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidosis on Isolated Porcine Retinal Vessels

Abstract: Acidosis-induced relaxation of the tone in preconstricted isolated porcine retinal arterioles is associated with a decrease in intracellular calcium and a hyperpolarization of the smooth muscle cells. The acidosis-induced relaxation is independent of CO(2) and is not mediated through NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Acidosis-induced relaxation of tone in preconstricted isolated porcine retinal arterioles is associated with a hyperpolarization and a decrease in [Ca 2+ ] i in the smooth muscle cells. The same study demonstrated that the vascular response to normocapnic and hypercapnic acidosis was similar, hence independent of CO 2 , and not mediated by NO (Hessellund et al, 2006). In isolated rat retinae, pharmacological inhibition of carbonic anhydrase, resulting in extracellular acidification, is associated with an increase in capillary diameter (Reber et al, 2003).…”
Section: Regulation Of Retinal Blood Flowmentioning
confidence: 86%
“…Acidosis-induced relaxation of tone in preconstricted isolated porcine retinal arterioles is associated with a hyperpolarization and a decrease in [Ca 2+ ] i in the smooth muscle cells. The same study demonstrated that the vascular response to normocapnic and hypercapnic acidosis was similar, hence independent of CO 2 , and not mediated by NO (Hessellund et al, 2006). In isolated rat retinae, pharmacological inhibition of carbonic anhydrase, resulting in extracellular acidification, is associated with an increase in capillary diameter (Reber et al, 2003).…”
Section: Regulation Of Retinal Blood Flowmentioning
confidence: 86%
“…In previous studies of the effect of prostaglandins on retinal vascular tone, initial contraction was induced by the thromboxane analogue U46619 (Holmgaard et al. 2008; Holmgaard & Bek 2010), as this compound can induce a reproducible concentration‐dependent vasocontraction in these vessels (Hessellund et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that in addition to KPSS, also endothelin‐1 and the thromboxane analogue U46619, but not NA, could constrict porcine retinal arterioles. U46619 induced a smaller constriction than endothelin‐1 and KPSS, whereas wire myograph studies have shown a large arteriolar contraction of all three compounds in porcine and bovine retinal arterioles (Delaey & Van de Voorde 1998; Hessellund et al. 2006; Holmgaard et al.…”
Section: Discussionmentioning
confidence: 98%
“…2008). The blood flow is determined by the arteriovenous pressure difference and the vessel diameter in the vascular system, but due to methodological limitations both in vitro and in vivo studies of diameter changes have hitherto largely been performed on retinal vessels with a diameter larger than approximately 100 μm (Delaey & Van de Voorde 2000; Hessellund et al. 2006; Torring et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation